Massive Chylous Ascites and Chylothorax Secondary to Chronic Pancreatitis: A Novel Surgical Option - Lee, Grace C.; Cetrulo, Curtis L.; Muniappan, Ashok; Yamada, Kei; Lillemoe, Keith D. (Journal of Reconstructive Microsurgery Open, 2020)
Background Chylous ascites is a debilitating condition characterized by milky, triglyceride-rich fluid accumulating in the peritoneum due to disruption of the intraabdominal lymphatic system. Medical management includes low-fat diets, somatostatin analogues, and therapeutic paracentesis, but is unsuccessful in one-third of patients.Methods We present a 59-year-old man with massive chylous ascites and chylothorax secondary to chronic pancreatitis, who failed medical therapies for nearly two years, before being successfully treated with a novel surgical technique. Demographic and clinical data were obtained from the electronic medical record at Massachusetts General Hospital from 2015 to 2019. Patient information was kept anonymous and informed consent was obtained for publication of this report.Results Based on a previously published small case series, we created a vascularized lymphatic cable flap based on the superior epigastric vessels, which we anastomosed to mesenteric vessels, permitting chylous drainage superiorly through the thoracic duct. With two years of follow-up, our patient has no evidence of recurrent ascites or chylothorax, and robust nutritional and functional status.Conclusion We present this novel surgical technique as a promising intervention for patients with chylous ascites and/or chylothorax who have failed medical management.
Keywords: chylous ascites; chyle leak; lymphatic flap